Technology and Overall Performance of Indonesian Manufacturing Firms: Do Manufacturing Strategies Serve as Moderators - Ellitan, Lena (Jurnal Widya Manajemen & Akuntansi, 2003)
Although there have been many studies focusing on the determinants of technological adoption and innovation, there is still a dearth of empirical results that relate to technology adoption and performance, especially in the Indonesian manufacturing sector. Based on the fact that the increased use of advanced manufacturing technologies and new management practices cannot be directly related to higher performance, this study tries to integrate technological and innovation considerations with manufacturing strategic development. This study focuses on the role of manufacturing strategy in moderating the impact of hard and soft technology on overall performance. The alignment between technology and manufacturing strategy is necessary to ensure success of firms. Data were collected through mailed questionnaires to CEOs of medium and large manufacturing firms in Indonesia.T his study finds that both hard and soft technologies have positive impacts on overall firm's performance. Further, manufacturing strategy plays an important moderating role on the relationship between technology and performance.